Approach to assessing the preparedness of hospitals to power outages - Brehovská, Lenka; Nešporová, Veronika; Řehák, David (Vysoká škola báňská - Technická univerzita Ostrava, 2017)
Within the secondary impacts of electricity blackouts, it is necessary to pay attention to facilities providing medical care for the population, namely the hospitals. Hospitals represent a key position in the provision of health care also in times of crisis. These facilities must provide constant care; it is therefore essential that the preparedness of such facilities is kept at a high level. The basic aim of this article is to analyse the preparedness of hospitals to power outages (power failures, blackouts) within a pilot study. On that basis, a SWOT analysis is used to determine strengths and weaknesses of the system of preparedness of hospitals to power outages and solutions for better security of hospitals are defined. The sample investigated consists of four hospitals founded by the Regional Authority (hospitals Nos. 1-4) and one hospital founded by the Ministry of Health of the Czech Republic (hospital No. 5). The results of the study shows that most weaknesses of the preparedness of hospitals are represented by inadequately addressed reserves of fuel for the main backup power supply, poor knowledge of employees who are insufficiently retrained, and old backup power supplies (even 35 years in some cases).
Keywords: Preparedness; hospitals; power outages; assessment; SWOT